Dilemmas of Intervention Social Science for Stabilization and Reconstruction - Davis, Paul K. (RAND Corporation, 2011)
Governments intervening in post-conflict states find themselves beset with numerous challenges and profound dilemmas: It is often unclear how best to proceed because measures that may improve conditions in one respect may undermine them in another. This volume reviews and integrates the scholarly social-science literature relevant to stabilization and reconstruction, with the goal of informing strategic planning at the whole-of-government level.